Reform of the New Criminal Procedure Code and the Challenges of Strengthening the Role of Advocates in Indonesia’s Criminal Justice System - Chitto Cumbhadrika; Muchlas Rowi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The reform of the Criminal Procedure Code (KUHAP) introduces new regulations regarding the position of advocates as law enforcers through Article 149, which includes the recognition and protection of professional immunity. It is seen as a progressive step in strengthening the role of advocates in the criminal justice system. However, the formulation of norms requiring the implementation of duties